If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -2(x + 1) = 3(2 + -1x) Reorder the terms: 6x + -2(1 + x) = 3(2 + -1x) 6x + (1 * -2 + x * -2) = 3(2 + -1x) 6x + (-2 + -2x) = 3(2 + -1x) Reorder the terms: -2 + 6x + -2x = 3(2 + -1x) Combine like terms: 6x + -2x = 4x -2 + 4x = 3(2 + -1x) -2 + 4x = (2 * 3 + -1x * 3) -2 + 4x = (6 + -3x) Solving -2 + 4x = 6 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -2 + 4x + 3x = 6 + -3x + 3x Combine like terms: 4x + 3x = 7x -2 + 7x = 6 + -3x + 3x Combine like terms: -3x + 3x = 0 -2 + 7x = 6 + 0 -2 + 7x = 6 Add '2' to each side of the equation. -2 + 2 + 7x = 6 + 2 Combine like terms: -2 + 2 = 0 0 + 7x = 6 + 2 7x = 6 + 2 Combine like terms: 6 + 2 = 8 7x = 8 Divide each side by '7'. x = 1.142857143 Simplifying x = 1.142857143
| (x+5)(2x+3)= | | n/2-2=12 | | 16277.76=4*3.14r^2 | | A=(7y+8)(2y-9) | | x^2+y^2-14y+49=49 | | y=5sen^2(9x) | | 7+2s-3=9s+13-6s | | 8(t-4)+4t=6(2t+2)-11 | | (4+1)x(10/2) | | 13m+39= | | 3logx=5 | | (7+w)(4w-6)=0 | | (2x^2-1)+2x^2-3=0 | | 6(2x-4)+5=3(2x+5) | | -(.5X-3)/4(X/5) | | 3(2x-5)-4=4(x+2) | | 5(2x+3)=3(2x+3) | | 3x+1=6x-y | | 4z-3/z+6 | | .5(7x/48) | | 3x-12/x=9 | | .5(5-7X)=8-(4X/6) | | 7x+22=2(5x+2) | | 3/2=4x+6/x | | 5(x*x-1)=4(x-1) | | (-3)*2+8=2x | | f(x)+f(y)-f(x+y)=xy | | 7/10+5/8 | | (x*7)+5=(x+7)*5 | | x^5+9x+10=0 | | sincx=0.707 | | 3x*x+1=0 |